Principles of psychospiritual intervention in addiction therapy: An islamic perspective - Zulfa Izza, Mohamed; Rohayah, Husain; Nasir, Mohamad; Nor Hidayah, Abu Bakar; Khairi, Che Mat (2016)
Drug addiction is a social disease of the new millennium that is increasingly worrying. This issue should be given serious attention and efforts to resolve it requires the cooperation of from all parties. Although the there are many method available for managing this problems, including the methadone maintenance therapy; the rate of remission is still low. Previous studies that have been conducted abroad revealed aspects of religion provide a significant positive effect on the symptoms of drug addiction. Psychospiritual intervention in addiction therapy aims to provide comprehensive opiate addiction management focusing on psychosocial and spiritual aspects of the clients. The principles that will be applied are the concept of mercy, patience, gratitude, khauf and raja'. Based on these principles, we aims to treat the client as a whole including physical, psychological and spiritual, based on the methods outlined by Islam derived from the Qur'an, al-Sunna, the pious and Islamic science.